A standardisable model of focal cerebral ischaemia innormotensive rats - (:unkn) unknown (My University, 1995)
In this study various techniques with different periods of ischaemia have been used in order to describe a standardisable and reproducible model of reversible focal cerebral ischaemia in normotensive rats. Cerebral blood flow to the left hemisphere of the rats was temporarily interrupted by middle cerebral artery occlusion only in four rats of each group, by simultaneous middle cerebral artery and ipsilateral common carotid artery occlusion in six rats of each group, and by middle cerebral artery and bilateral common carotid artery occlusion in six rats of each group. Within each group temporary ischaemia lasted for 1, 2 or 3 h and animals survived for 24 h following reperfusion. An infarct of significant size with low standard deviation was observed after 3 h of distal middle cerebral artery and bilateral common carotid artery occlusion followed by 24 h of reperfusion. We have found that the ratio of the infarct volume to the supratentorial brain volume is a more reliable criterion (with less standard deviation) than infarct volume alone and could be used for comparison of results obtained in experimental studies. © 1995 Pearson Professional (Australia) Pty Ltd.
Keywords: Animal model; Focal cerebral ischaemia; Middle cerebral artery; Reperfusion; Stroke